2022
DOI: 10.7759/cureus.23485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Long-Term Efficacy of Home-Based Versus Center-Based Cardiac Rehabilitation

Abstract: Cardiac rehabilitation programs support the health, wellness, and recovery of patients with cardiovascular conditions. This systematic review attempts to expand these findings while analyzing the latest randomized controlled trials (RCTs) focusing on the long-term advantages of home/center-based cardiac rehabilitation interventions. This study also comparatively analyzes the benefits of opting for home-based cardiac rehabilitation instead of center-based measures to improve the long-term clinical outcomes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Previous studies have shown no significant differences between home-based and hospital-based CR in terms of functional capacity, psychological symptoms, quality of life, and all-cause hospitalization. 7 , 9 In addition, a recent systematic review has shown that home CR can be a safe alternative to CR. 37 Despite this, most patients prefer hospital-based compared with home-based CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown no significant differences between home-based and hospital-based CR in terms of functional capacity, psychological symptoms, quality of life, and all-cause hospitalization. 7 , 9 In addition, a recent systematic review has shown that home CR can be a safe alternative to CR. 37 Despite this, most patients prefer hospital-based compared with home-based CR.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In addition, technology-assisted home CR can extend healthcare support to more patients, and patients from rural areas have more access to CR. 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible alternative way of delivering CR in SA as home-based CR which could be one of the solution to overcome the barriers of limited number of CR in the western region of SA. Home-based CR may help on removing barriers, 32 because it has easy access for cardiac patients particularly to those who lives in the rural areas, it is suitable to use during the pandemic such as COPVID and patients can use telehealth during home-based CR centers. 15,33,34…”
Section: Dovepressmentioning
confidence: 99%
“…[ 9 ] It not only guarantees the accessibility of CR during the COVID-19 pandemic, but also provides better opportunities for patients in rural or other backward areas to participate in CR. [ 10 , 11 ] The latest meta-analysis indicates that HBCR with wearable sensors has the potential to increase the accessibility, adherence, and participation rates in CR interventions, by helping to overcome several barriers that prevent CR participation. [ 12 ] Overall, home-based cardiac rehabilitation has a promising future.…”
Section: Introductionmentioning
confidence: 99%